Sub-National policy readiness as regards the planet’s carrying capacity and environmental sustainability in Kenya (Journal of Sustainability, Environment and Peace, 2019)
The achievement of global sustainable development goals subject to planetary boundaries will mostly be determined at national  and at sub-national level as regards contribution to cultures, economies, material use, and waste generation. This paper seeks to investigate planetary and Kenya’s county boundaries as development targets from a county development plan perspective.  The methodology provides an important tool for counties to play a more fulsome and active role in global sustainable development. Content analysis of the  nine limits, namely: climate change, novel entities, ozone depletion, aerosol loading, ocean acidification, biogeochemical flows, freshwater use, land-system change, and biosphere integrity, was performed in the context of  the  respective County Integrated Development Plans (CIDPs) 2018-2023. A total of 22 CIDPs for 22 counties are analysed to capture the content entailing issues pertaining to the above nine limits. Correlation analysis of the counts of the limits were generated and discussed. It was observed that the CIDPs cover between 30 to 60% of the expected content of the limits. This is a pointer to the extent to which the counties, and hence Kenya as a country, are ready as regards addressing planetary boundaries at local level. Further, correlation analysis on the counts on planetary boundaries versus peace issues revealed positive correlation between biodiversity and peace, with a correlation coefficient of 0.575. It is interesting to observe that the counties having strategies on biodiversity have associate peace initiatives. This is a pointer that promotion of biodiversity conservation is closely relate to peaceful outcomes.
Keywords: Sustainability; planetary boundaries; county intergrated development plans; peace